State intervention in sciences - Long, Hoang Xuan; Chi, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Three categories of science: the science as cosmos religion, the science for the State and the science for enterprises which are different in their features of motivations of activities. Motivations of the science as cosmos religion are based mainly on faiths, aspiration and sacrifice spirits. Motivations of the science for the State target values and interests of the State and the nation. Motivations of the science for enterhprises are related to production activities and competitions in business activities. The scope and the level of State interventions are also different from one category to another one. These remarks serve as background for proposal of new directions of management activities to meet features of every category of science including their motivations, orientations, modes of investment and specific modes of management. Code: 17112201